Modern food service purchasing - Garlough, Robert (Australia : Delmar Cengage Learning, 2011)
Covering the essential purchasing concepts, storeroom operations, and financial stewardship, this title addresses the needs of the executive chef. It presents the four fundamentals in foodservice purchasing: market and distribution systems, storeroom operations, cost controls and product information.
Part I. Procurement: Dynamics of Food Service Purchasing.1. The Purchasing Function: An Overview.2. Food Laws and the Market and Distribution Systems.3. Practical Considerations for Buying Decisions4. Modern Applications of Food Science.Part II. Purchasing Management: Mastering the Storeroom.5. Measuring and Packaging for Preservation, Sale, and Distribution.6. The Ingredient Process.7. The Physical Storeroom.8. Receiving, Storing, and Issuing.9. Cost Control Measures for Food Service Operations.10. Security Issues with Vendors, Employees and Customers. Part III. The Commodities: Developing Product Knowledge.11. Herbs, Spices, Minerals, and Flavoring Agents.12. Bakery Supplies.13. Meats and Offal.14. Poultry and Game.15. Fish and Shellfish.16. Fruits. 17. Vegetables. 18. Eggs, Dairy, and Cheese.19. Vegetarian and Special Dietary Products.20. Beverages.21. Postscript: Futurist Thoughts on Food Service
Includes index.
Keywords: FOOD SERVICE PURCHASING